Considerações sobre o problema do gosto em Kant (Razão e Fé, 2024)
Taking into consideration the current aesthetic relativism, this lecture presents contributions from Kant’s theory of aesthetic intersubjectivity to the problem of the validity of the judgment of taste. For this, it contextualizes the Kantian intersubjectivism proposed in the Third Critique within aesthetics, exposes notions about its contents and a priori grounds, and raises challenging questions for its reception in the present day.